La medicina en la obra de Michel Foucault : Meta-síntesis. (2018)
Michel Foucault has had an impact on public healths; however, analysis of his works about medicine have been marginal. The objective of this research was to characterize the scientific publications related with medicine in the work of the French philosopher, following the phases of identification, screening, eligibility and inclusion of PRISMA guide. The incidence of Foucault in medical anthropology and medical sociology is clear. However, one of the topics with less research is Foucault's contribution to the field of medical ethics. These findings constitute a valuable input to improve research on the ontology of the present, from Foucaultian methodologies, in areas little explored such as evidence-based medicine, the molecularization of clinical diagnosis, the growing interest in neuroscience discourse and self-management of welfare, driven by the dynamics of "advanced liberal" government.